2023
DOI: 10.1098/rsta.2022.0125
|View full text |Cite
|
Sign up to set email alerts
|

Taylor–Couette flow of hard-sphere suspensions: overview of current understanding

Abstract: Although inertial particle-laden flows occur in a wide range of industrial and natural processes, there is both a lack of fundamental understanding of these flows and continuum-level governing equations needed to predict transport and particle distribution. Towards this effort, the Taylor–Couette flow (TCF) system has been used recently to study the flow behaviour of particle-laden fluids under inertia. This article provides an overview of experimental, theoretical and computational work related to the TCF of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Recent investigations by Majji et al (2018) andRamesh et al (2019) and the review by Baroudi et al (2023) provide detailed insight into the characteristics of Taylor-Couette flow for neutrally buoyant suspensions. In a concentric cylinder cell of 5.5 ≤ ζ ≤ 11 and 0.84 ≤ η ≤ 0.914, Ramesh et al (2019) collected simultaneous measurements of torque and PIV observations, and discovered a variety of flow regimes developing in response to several variables, including ζ , η, solid fraction (which varied in the range 0.1 < φ < 0.25) and rotational acceleration (increasing from rest or decreasing from maximum speed).…”
Section: Neutrally Buoyant Suspensions and The Krieger-dougherty Effe...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent investigations by Majji et al (2018) andRamesh et al (2019) and the review by Baroudi et al (2023) provide detailed insight into the characteristics of Taylor-Couette flow for neutrally buoyant suspensions. In a concentric cylinder cell of 5.5 ≤ ζ ≤ 11 and 0.84 ≤ η ≤ 0.914, Ramesh et al (2019) collected simultaneous measurements of torque and PIV observations, and discovered a variety of flow regimes developing in response to several variables, including ζ , η, solid fraction (which varied in the range 0.1 < φ < 0.25) and rotational acceleration (increasing from rest or decreasing from maximum speed).…”
Section: Neutrally Buoyant Suspensions and The Krieger-dougherty Effe...mentioning
confidence: 99%
“…(2019) and the review by Baroudi et al. (2023) provide detailed insight into the characteristics of Taylor–Couette flow for neutrally buoyant suspensions. In a concentric cylinder cell of and , Ramesh et al.…”
Section: Prior Studiesmentioning
confidence: 99%
“…The resulting structure was explained as a competition between interaction with the walls and drift in the complex shear gradient, due to Taylor vortices, finally resulting in a limit cycle for position. Furthermore, more recent studies (Majji, Banerjee & Morris 2018;Baroudi et al 2023) have shown that particles significantly impact the qualitative nature of the Taylor-Couette flow dynamical system.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, more recent studies (Majji, Banerjee & Morris 2018; Baroudi et al. 2023) have shown that particles significantly impact the qualitative nature of the Taylor–Couette flow dynamical system.…”
Section: Introductionmentioning
confidence: 99%
“…Part 1 of this two-part theme issue explored contemporary topics related to Taylor-Couette flow including turbulent, convective and two-phase flows as well as extensions to magnetohydrodynamic, ferrofluidic and viscoelastic flows and flow geometries that are closely related to the Taylor-Couette problem [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Part 2 of this theme issue continues with review articles and research articles having their origin in Taylor's 1923 paper.…”
mentioning
confidence: 99%